Answer:
y * ( 6*5)
Step-by-step explanation:
(y x 6) x 5
We can change the order of multiplication by changing where the parentheses are placed using the associative property
y * ( 6*5)
Answer:
Any negative and positive number can be your coordinates.
Step-by-step explanation:
As long as you don't have any restrictions as to what the coordinates can be, you're good to go!
Hope this helps!
(2,8) and (-2,10)
<u>y₂</u><u> </u><u>- y₁</u> used to find the slope<u>
</u>x₂ - x₁
<u>
</u>plug in the coordinates
<u>10-8</u> = <u>2</u> all equals -1/2
-2-2 = -4 m=-1/2
<u>
</u>plug one of the coordinates and the slope into y=mx+b, and solve
<u />8=-1/2(2)+b
8=-1+b
9=b
Final Answer: y = -1/2x + 9
Answer:
Brooklyn is more expensive
Step-by-step explanation:
The equation that has an infinite number of solutions is ![2x + 3 = \frac{1}{2}(4x + 2) + 2](https://tex.z-dn.net/?f=2x%20%2B%203%20%3D%20%5Cfrac%7B1%7D%7B2%7D%284x%20%2B%202%29%20%2B%202)
<h3>How to determine the equation?</h3>
An equation that has an infinite number of solutions would be in the form
a = a
This means that both sides of the equation would be the same
Start by simplifying the options
3(x – 1) = x + 2(x + 1) + 1
3x - 3 = x + 3x + 2 + 1
3x - 3 = 4x + 3
Evaluate
x = 6 ----- one solution
x – 4(x + 1) = –3(x + 1) + 1
x - 4x - 4 = -3x - 3 + 1
-3x - 4 = -3x - 2
-4 = -2 ---- no solution
![2x + 3 = \frac{1}{2}(4x + 2) + 2](https://tex.z-dn.net/?f=2x%20%2B%203%20%3D%20%5Cfrac%7B1%7D%7B2%7D%284x%20%2B%202%29%20%2B%202)
2x + 3 = 2x + 1 + 2
2x + 3 = 2x + 3
Subtract 2x
3 = 3 ---- infinite solution
Hence, the equation that has an infinite number of solutions is ![2x + 3 = \frac{1}{2}(4x + 2) + 2](https://tex.z-dn.net/?f=2x%20%2B%203%20%3D%20%5Cfrac%7B1%7D%7B2%7D%284x%20%2B%202%29%20%2B%202)
Read more about equations at:
brainly.com/question/15349799
#SPJ1
<u>Complete question</u>
Which equation has infinite solutions?
3(x – 1) = x + 2(x + 1) + 1
x – 4(x + 1) = –3(x + 1) + 1
![2x + 3 = \frac{1}{2}(4x + 2) + 2](https://tex.z-dn.net/?f=2x%20%2B%203%20%3D%20%5Cfrac%7B1%7D%7B2%7D%284x%20%2B%202%29%20%2B%202)
![\frac 13(6x - 3) = 3(x + 1) - x - 2](https://tex.z-dn.net/?f=%5Cfrac%2013%286x%20-%203%29%20%3D%203%28x%20%2B%201%29%20-%20x%20-%202)